Avaliação da sustentabilidade com a adoção de desenvolvimento de produto sustentável circular em empresas do setor de autopeças - Silva, Carlos Augusto Borges da (2024)
In the last years, society has been enforcing the manufacturing sectors to have greater environmental awareness for population wellness. It is encouraged by companies to have products in their portfolios that meet various environmental and sustainability trends that cover the use of a Circular Economy strategy. However, companies have economic and operational metrics that must be incorporated into macro environmental and social strategies in order to be supported by senior corporate management. Therefore, the need for Design for Environment and Ecodesign practices from before the start of the development process of a new sustainable product is important. In this context, the general objective of this work aims to evaluate the economic, environmental and social gains of adopting Sustainable Product Development (SPD) considering the Circular Economy (CE) in auto parts companies located in Brazil. The method used was a case study, carried out in one company producing parts for the automotive sector, where a proposal for the SPD framework considering the CE and a checklist were applied that served as a guide for the design and development stages of a sustainable product. As a result, it was verified that the SPD framework is fully applicable considering the proposed CE from the product design stage to the stages prior to production, with the application of the checklist that will serve as a guide for the implementation of SPD practices and reflecting in economic, environmental and social gains as demonstrated in the Case Study proposed in this work.